2011
DOI: 10.4028/www.scientific.net/amr.320.456
|View full text |Cite
|
Sign up to set email alerts
|

Increase Characteristics of Local Wall Thickness of a Pipe during Die Forming

Abstract: In recent years global warming has become a worldwide problem. Reduction of carbon dioxide emissions is one of the most important issues also in the automobile industry. This weight reduction technology is important even if applied to electric vehicles rather than gasoline vehicles, as reduction of energy consumption is an important issue. Plastic processing of hollow pipes is an important technology for realizing weight reduction of automobile components. As an example of research into pipe forming there is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…2. Because of this load in t axial direction, if the pipe diameter becomes too small, buckling of the pipe will occur similar to the method of increasing wall thickness by shortening the pipe length It was reported that compression up to a diameter of 26mm is possible in a pipe with a diameter of 30mm, a wall thickness of 2mm and a length of 100mm [6]. According to similar analysis, with a pipe with the same diameter of 30mm but with a length of 200mm and a thickness of 3mm, if the bottom edge of the pipe is fixed in the die, buckling occurs at compression to a diameter of 28mm, as shown in Fig.…”
Section: Increases In Pipe Wall Thickness Due To Pipe Compressionmentioning
confidence: 99%
“…2. Because of this load in t axial direction, if the pipe diameter becomes too small, buckling of the pipe will occur similar to the method of increasing wall thickness by shortening the pipe length It was reported that compression up to a diameter of 26mm is possible in a pipe with a diameter of 30mm, a wall thickness of 2mm and a length of 100mm [6]. According to similar analysis, with a pipe with the same diameter of 30mm but with a length of 200mm and a thickness of 3mm, if the bottom edge of the pipe is fixed in the die, buckling occurs at compression to a diameter of 28mm, as shown in Fig.…”
Section: Increases In Pipe Wall Thickness Due To Pipe Compressionmentioning
confidence: 99%
“…They suppressed reduction in wall thickness and achieved greater pipe expansion than by hydroforming. Kotani et al [3][4][5][6][7][8] used finite-element analysis to predict the wall thickness increase of aluminum pipe with 2mm wall thickness when its diameter was reduced. Kamei [9][10][11][12] This research investigated a method of increasing the wall thickness of steel pipe by pressing.…”
Section: Introductionmentioning
confidence: 99%
“…They suppressed reduction in wall thickness and achieved greater pipe expansion than by hydroforming. Kotani et al [3] used finite-element analysis to predict the wall thickness increase of aluminum pipe with 2mm wall thickness when its diameter was reduced. This research investigated a method of increasing the wall thickness of steel pipe by pressing.…”
mentioning
confidence: 99%